Identifying the influence of inhomogeneities in multimode optical fibers on the quality of signal transmission - Ospanova, Nurzhamal; Orazymbetova, Aigul; Bakhtiyarova, Yelena; Lipskaya, Marina; Beibit, Yerdaulet (Eastern-European Journal of Enterprise Technologies, 2025)
The object of this study is fiber-optic communication lines operating under increased mechanical loads arising during cable installation, operation in aggressive environments, or on moving objects. The problem lies in the insufficient understanding of the impact of mechanical loads on the parameters of optical fibers, which complicates their use in challenging operating conditions. The aim of the work is to improve the reliability and durability of such lines by studying the effect of tensile and compressive loads on the characteristics of multimode optical fibers (MOFs). During the experiments, the initial attenuation values (1.09 dB/km) and their changes under tensile loads were measured. Test samples, approximately 20 meters long, were subjected to gradually increasing tensile force. Prolonged exposure to the load significantly increased the attenuation coefficient, particularly in the shortwave part of the spectrum. Fiber failure occurred after 113 minutes, indicating a critical reduction in strength. This effect can be attributed to the intensification of material inhomogeneities in the fiber, leading to increased light scattering. The impact of compressive loads on dispersion was studied at a wavelength of 1.06 μm. It was found that the shortwave spectrum is more sensitive to deformations due to the specific structure of the fiber. A comprehensive analysis of the loads identified critical factors affecting the reliability of MOFs. The results obtained enable the prediction of the durability of fiber-optic communication lines, accounting for mechanical impacts in their design and developing recommendations for improved operation. The practical significance lies in applying the findings to enhance fiber condition assessment methods and create more reliable communication systems